PENGARUH LINGKUNGAN BUDAYA PENDIDIKAN TERHADAP INTENSITAS PERAN AKUNTANSI MANAJEMEN PADA PERGURUAN TINGGI DI PROVINSI NANGGROE ACEH DARUSSALAM - Mulyadi Abdurrahman (Jurnal Akuntansi Muhammadiyah (JAM), 2010)
Accounting practice is not just technical, but also a social practice and culture, as social and cultural practices, accounting course is not a stuck, it could have the power to affect the social life of the people (Rashid, 2002:6), even as the son of local culture (Masturi, 2003:3). Accounting education is needed as the factor as a function of culture and control, it can also have a strong influence on the intensity of management accounting role within the scope of higher education. Previous findings showed that there is a gap between academics and practitioners, no doubt management accountant position himself as advisers and managers are not confident about the reliability of the techniques of management accounting. (Rashid, 1998; Son, and Naim, 2000:282Instruments used consists of the dimensions of the cultural characteristics and intensity of management accounting role include management accounting information systems, decision making, and planning and control developed by Hofstede et., All (1990). Population and study take sample from leaders/managers, teachers / lecturers, and academic staff / finance at several universities in the province of Aceh through questionnaires of 197 respondents, and 132 questionnaire return rate of respondents (67%). Method of analysis performed using regression analysis, and data processing performed using SPPS version 12.These results has indicating in the higher education cultural environment that characterized the results orientation IPAM have rates higher than the cultural characteristics of the process, the same result has obtained that the cultural environment characterized by a closed system has IPAM higher rates than open systems. Overall environmental impact of the educational culture IPAM in PT in the Province of Nanggroe Aceh Darussalam for 21.5%., And the remaining 78.5% influenced by other factors Keywords: Culture, Environment Education, and The intensity of Management Accounting Role